2018
DOI: 10.1016/j.tre.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a satellite network with direct delivery in the pharmaceutical industry

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…The second most addressed problem type was spatial analysis, which represents 32.74% of the papers. All the studies that performed some level of descriptive analysis, inference, or observation of spatial properties of events used [13], [44], [45], [47]- [50], [52]- [55], [60], [64], [65], [76], [78], [80]- [91], [95]- [97], [101], [102], [104], [107]- [109], [111]- [115], [117], [118], [121], [126], [138], [143]- [148], [150]- [152], [155], [157], [159], [161], [163], [166]- [171], [174]- [184], [186], [192], [196], [198], [199] Spatial analysis 55 32.74% [11],…”
Section: A Problem Type Findingsmentioning
confidence: 99%
“…The second most addressed problem type was spatial analysis, which represents 32.74% of the papers. All the studies that performed some level of descriptive analysis, inference, or observation of spatial properties of events used [13], [44], [45], [47]- [50], [52]- [55], [60], [64], [65], [76], [78], [80]- [91], [95]- [97], [101], [102], [104], [107]- [109], [111]- [115], [117], [118], [121], [126], [138], [143]- [148], [150]- [152], [155], [157], [159], [161], [163], [166]- [171], [174]- [184], [186], [192], [196], [198], [199] Spatial analysis 55 32.74% [11],…”
Section: A Problem Type Findingsmentioning
confidence: 99%
“…Within [17,Figs. 1,2,[5][6][7][8], the SAVLR method showed the advantage over the above SLR method to solve GAPs. For completeness of comparison with the newly-developed SLBLR method, SAVLR is also included in Table 3.…”
Section: Discussionmentioning
confidence: 94%
“…Although the delivery for medications has been increasingly implemented, based on the recent literature reviews, we found that only a few studies—for example, Fathollahi Fard et al 3 , Veenstra et al 6 , and Zhu and Ursavas 26 —have solved the logistics problem of medication delivery to determine the locations of potential facilities and the vehicle routing simultaneously. In this work, we extend the framework derived from Veenstra et al, 6 which investigates the joint facility location and VRP for medication delivery through lockers and customers’ homes.…”
Section: Discussionmentioning
confidence: 99%
“…They included two subpopulations derived from feasible solutions and infeasible solutions similar to the work by Yu et al 17 LRPs have been particularly applied in the real-world case with practical instances to increase efficient distribution networks and to increase competitiveness in the recent market. Some realworld case studies were presented by Veenstra et al 6 and Zhu and Ursavas, 26 which solved the LRP for the medication distribution in the Netherlands. The proposed model by Zhu and Ursavas 26 determined the facility and routing decisions simultaneously by considering three node types: depots, satellites, and customers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation